Analisis Gaya Mengajar Guru SMA Terhadap Minat Belajar Siswa - Lekahena, Welly Sany; Naibaho, Lamhot; Rantung, Djoys Anneke (Jurnal Kridatama Sains dan Teknologi, 2024)
This research aims to analyze the relationship between teachers' teaching styles at the high school level and students' interest in learning. Student interest in learning is an important factor in achieving optimal learning outcomes. Problems that often occur in the classroom are incompatibility of teaching styles with student needs, lack of creativity and innovation, lack of interaction and participation, not being aware of the diversity of student learning styles, and lack of use of educational technology. Therefore, this research was conducted to determine the influence of high school teachers' teaching styles on students' interest in learning. The method used in this research is literature study. The results of the analysis show that there is a correlation between the teacher's teaching style and students' learning interest. A teaching style that is interactive, supports student participation, and motivates their creativity tends to have a positive impact on interest in learning. On the other hand, a teaching style that is monotonous and less interactive can potentially reduce students' interest in learning. These findings provide important implications for the development of teaching methods in high school, by emphasizing the need to pay attention to teaching styles that can stimulate students' interest in learning. This research can be a basis for preparing guidelines for developing teacher professionalism and improving the education system that focuses on the quality of learning at the high school level.